Parasporin, a Human Leukemic Cell-Recognizing Parasporal Protein of Bacillus thuringiensis - Mizuki, Eiichi (American Society for Microbiology, 2000)
An unusual property, human leukemic cell-recognizing activity, associated with parasporal inclusions of a noninsecticidal Bacillus thuringiensis soil isolate was investigated, and a protein (named parasporin in this study) responsible for the activity was cloned. The parasporin, encoded by a gene 2,169 bp long, was a polypeptide of 723 amino acid residues with a predicted molecular weight of 81,045. The sequence of parasporin contained the five conserved blocks commonly found in B. thuringiensis Cry proteins; however, only very low homologies (<25%) between parasporin and the existing classes of Cry and Cyt proteins were detected. Parasporin exhibited cytocidal activity only when degraded by proteases into smaller molecules of 40 to 60 kDa. Trypsin and proteinase K activated parasporin, while chymotrypsin did not. The activated parasporin showed strong cytocidal activity against human leukemic T cells (MOLT-4) and human uterus cervix cancer cells (HeLa) but not against normal T cells.